2016
DOI: 10.1177/0022002716678986
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Religious Radicalization

Abstract: A variety of theories attempt to explain why some individuals radicalize along religious lines. Few studies, however, have jointly put these diverse hypotheses under empirical scrutiny. Focusing on Muslim-Christian tensions in Kenya, we distill salient micro-, meso-, and macro-level hypotheses that try to account for the recent spike in religious radicalization. We use an empirical strategy that compares survey evidence from Christian and Muslim respondents with differing degrees of religious radicalization. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 59 publications
0
33
0
1
Order By: Relevance
“…Even minor, seemingly unrelated, threats induced in the lab can lead to ideological extremism: Attempts to understand an incomprehensible (vs. a simple) text passage that was said to be diagnostic of academic abilities resulted in greater endorsement of religious zeal on items such as "If I really had to, I would give my life for my religious beliefs" (McGregor et al 2010). Hundreds of similar experiments indicate that environmental threats move individuals toward diverse varieties of ideological zeal, with or without involvement of group processes, to help dampen threat-induced distress (McGregor 2003;reviewed in Jonas et al 2014), an effect that holds when controlling for macro-level factors such as political and economic grievances (Rink & Sharma 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even minor, seemingly unrelated, threats induced in the lab can lead to ideological extremism: Attempts to understand an incomprehensible (vs. a simple) text passage that was said to be diagnostic of academic abilities resulted in greater endorsement of religious zeal on items such as "If I really had to, I would give my life for my religious beliefs" (McGregor et al 2010). Hundreds of similar experiments indicate that environmental threats move individuals toward diverse varieties of ideological zeal, with or without involvement of group processes, to help dampen threat-induced distress (McGregor 2003;reviewed in Jonas et al 2014), an effect that holds when controlling for macro-level factors such as political and economic grievances (Rink & Sharma 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that specific scriptural passages help encourage violence (Bushman et al 2007), and religious beliefs have been found to play a key role in explaining religious extremism (Appleby 1999;Dawson 2018;Dawson & Amarasingam 2017;Wood 2016). In some cases, religiosity has been found to correlate with the increased endorsement of violent self-sacrifice (Cinnirella et al 2010;Rink & Sharma 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other factors include being affected or motivated by social structures and certain other specific issues at the micro and macro levels. 127 To illustrate, as a response to the question of why and how a subject integrated into the TH, he/she stated that:…”
Section: Variablesmentioning
confidence: 99%
“…Radicals may, for example, champion the protection of vanishing traditions (Calhoun 2012), or express intolerance of existing social and political systems (Nasr 2005;Achilov and Sen 2017). Some radicals may justify violence against innocents (Moskalenko and McCauley 2009;Snow and Cross 2011;Rink and Sharma 2018) and glorify death (Roy 2017), whereas others may pursue nonviolent extra-institutional action (Dalgaard-Nielsen 2010; Borum 2011; Bartlett and Miller 2012;Beck 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In an empirical parallel, the kind of radical that has lately attracted the most attention, so-called global jihadists, are nearly always portrayed as advocates of violence against external enemies (e.g. Benjamin and Simon 2002;Gambetta and Hertog 2016;Walter 2017b;Rink and Sharma 2018;Mitts 2019). However, recent events suggest radicalism may comprise a range of rhetorics.…”
Section: Introductionmentioning
confidence: 99%